Analysis of the vascular patterns of 52 amelanotic cutaneous melanoma metastases: a prospective descriptive study - Popović, Danijela; Mijušković, Željko; Jović, Andrija; Cekić, Sladjana; Vidović, Nataša; Tiodorović, Danica (Vojnosanitetski pregled, 2024)
Background/Aim. Early diagnosis of amelanotic cutaneous melanoma metastases (ACMM) represents a great challenge and is essential for determining the stage, treatment, and prognosis of the disease. The aim of the study was to evaluate the vascular structures and their arrangement and frequency in ACMM. Methods. The study was conducted as a prospective, descriptive, multicenter study of pathohistologically confirmed ACMM. Results. The study included a total of 52 ACMM from 17 patients (8 men and 9 women, with an age range of 32–91 years, median 63.12 years) with a previous history of primary melanoma. The most prevalent were elevated ACMM – 39 (75.0%) lesions, while 13 (25.0%) ACMM were flat. Linear irregular blood vessels were statistically significantly more often associated with elevated ACMM, compared to flat ACMM (92.3% vs. 50.0%, p < 0.001). Dotted blood vessels were statistically significantly more frequent in flat ACMM, compared to elevated ACMM (76.9% vs. 28.2%, p = 0.003). Diffuse distribution of blood vessels was the most prevalent, with 92.3% of flat ACMM and 76.9% of elevated ACMM (p = 0.416). Peripheral arrangement of blood vessels was detected in 15.4% of elevated ACMM and 7.7% of flat ACMM (p = 0.815). The central arrangement of blood vessels was seen in 2.6%, while the cluster (segmental) schedule was present in 5.1% of elevated ACMM. The monomorphic vascular pattern was the predominant pattern in 84.6% of flat ACMM and 61.5% of elevated ACMM (p = 0.232). Conclusion. Our study supports the finding that linear irregular blood vessels are more commonly associated with elevated ACMM, while the dotted ones are dominant in flat ACMM.